Lower respiratory tract infection hospitalizations among American Indian/Alaska Native adults, Indian Health Service and Alaska Region, 1998–2014. (October 2021) - Bruce, Michael G.; Bressler, Sara S.; Apostolou, Andria; Singleton, Rosalyn J.
Highlights: Lower respiratory tract infection (LRTI) rates increased 26% among Alaska American Indian/Alaska Native adults, compared to a 38% decrease in non-Alaska American Indian/Alaska Native adults. LRTI rates were higher in Alaska compared to non-Alaska. The most common diagnosis associated with LRTI was pneumonia, followed by essential hypertension. The median length of hospital stay was longer in Alaska compared to non-Alaska sites. A lack of piped water and household crowding likely contributed to the high rates of LRTI. Abstract: Objectives: This study describes the changes in lower respiratory tract infection (LRTI) rates from 1998 to 2014 among hospitalized American Indian/Alaska Native (AI/AN) adults residing in Alaska and other Indian Health Service (IHS) regions. Methods: Age-adjusted hospital discharge rates and rate ratios were calculated from the IHS Direct and Contract Health Services Inpatient Dataset, IHS National Patient Information Reporting System for AI/AN adults ≥18 years, hospitalized at an IHS-operated, tribally operated, or contract hospital with an LRTI-associated diagnosis during 1998–2014. Results: Overall, there were 13 733 LRTI-associated hospitalizations in Alaska (1998–2014), with an age-adjusted rate of 13.7/1000 adults. Among non-Alaska (non-AK) AI/AN, there were a total of 79 170 hospitalizations, with a rate of 8.6/1000 adults. In the pre-PCV7 and pre-PCV13 periods, LRTI rates were higher in Alaska (AK) AI/AN (12.4 and 14.1, respectively) when compared to non-AK AI/AN (10.1 and 9.1, respectively) ( P < 0.0001). In the post-PCV7 and post-PCV13 periods, LRTI rates were also higher in AK (13.5 and 15.0, respectively) compared to non-AK (9.2 and 7.3, respectively) ( P < 0.0001). Conclusions: Over the study period, a 26% increase in rates of LRTI among adult AI/AN residing in AK compared with a 38% decrease in rates among AI/AN residing in non-AK were observed. This disparity is likely due to a variety of factors such as tobacco use, crowding, etc. Strategies to reduce LRTI in AI/AN adults are needed.